2010
DOI: 10.1073/pnas.0910335107
|View full text |Cite
|
Sign up to set email alerts
|

Exotic behavior and crystal structures of calcium under pressure

Abstract: Experimental studies established that calcium undergoes several counterintuitive transitions under pressure: fcc → bcc → simple cubic → Ca-IV → Ca-V, and becomes a good superconductor in the simple cubic and higher-pressure phases. Here, using ab initio evolutionary simulations, we explore the behavior of Ca under pressure and find a number of new phases. Our structural sequence differs from the traditional picture for Ca, but is similar to that for Sr. The β-tin (I4 1 ∕amd) structure, rather than simple cubic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
78
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 49 publications
(126 reference statements)
8
78
0
Order By: Relevance
“…To overcome this discrepancy, Teweldeberhan et al (16) used diffusion quantum Monte Carlo calculations, Errea et al (18) used ab initio methods including anharmonic effects to stabilize the sc phase at room temperature, and Yao et al (17) provided a detailed analysis of ab initio molecular dynamics simulations that could account for the stability of the sc structure at room temperature. The remaining major discrepancy is that Yao et al (14) and Oganov et al (13) predicted that Ca with I4 1 ∕amd symmetry (β-tin structure) has a much lower zero-temperature enthalpy than sc, but in spite of many experimental efforts, the presumably more stable β-tin structured Ca has never been discovered. Here we report the search and discovery of the β-tin structured Ca and establish its stability range.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…To overcome this discrepancy, Teweldeberhan et al (16) used diffusion quantum Monte Carlo calculations, Errea et al (18) used ab initio methods including anharmonic effects to stabilize the sc phase at room temperature, and Yao et al (17) provided a detailed analysis of ab initio molecular dynamics simulations that could account for the stability of the sc structure at room temperature. The remaining major discrepancy is that Yao et al (14) and Oganov et al (13) predicted that Ca with I4 1 ∕amd symmetry (β-tin structure) has a much lower zero-temperature enthalpy than sc, but in spite of many experimental efforts, the presumably more stable β-tin structured Ca has never been discovered. Here we report the search and discovery of the β-tin structured Ca and establish its stability range.…”
mentioning
confidence: 96%
“…Very recently, Tse et al (22) also conducted low-temperature experiments to study the Ca sc phase; their results showed a large and anisotropic vibrations in sc Ca unit cell over a large pressure range at low temperatures. However, although the enthalpy of predicted β-tin structure Ca at 40 GPa is about 50 meV more favorable than sc structure (13,16,23), there have been no experimental observations of the predicted I4 1 ∕amd phase until now. To further investigate the stability of the Ca sc phase and to search for the possible I4 1 ∕amd tetragonal phase, we performed synchrotron X-ray diffraction (XRD) experiments on Ca through various low-temperature, high-pressure paths.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In brief, sX-LDA functional treats d electron differently compared to other functionals, 22,36,[42][43][44][45] PBE and LDA, see Fig. 4.…”
Section: Figmentioning
confidence: 99%